LncRNA Expression Profiles in Systemic Lupus Erythematosus and Rheumatoid Arthritis: Emerging Biomarkers and Therapeutic Targets - Wu, Han; Chen, Shuxian; Li, Aifen; Shen, Kangyuan; Wang, Shuting; Wang, Sijie; Wu, Ping; Luo, Wenying; Pan, Qingjun (Frontiers in Immunology, 2021)
Systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) are two common multisystem autoimmune diseases that share, among others, many clinical manifestations and serological features. The role of long non-coding RNAs (lncRNAs) has been of particular interest in the pathogenesis of autoimmune diseases. Here, we aimed to summarize the roles of lncRNAs as emerging novel biomarkers and therapeutic targets in SLE and RA. We conducted a narrative review summarizing original articles on lncRNAs associated with SLE and RA, published until November 1, 2021. Based on the studies on lncRNA expression profiles in samples (including PBMCs, serum, and exosomes), it was noted that most of the current research is focused on investigating the regulatory mechanisms of these lncRNAs in SLE and/or RA. Several lncRNAs have been hypothesized to play key roles in these diseases. In SLE, lncRNAs such as GAS5, NEAT1, TUG1, linc0949, and linc0597 are dysregulated and may serve as emerging novel biomarkers and therapeutic targets. In RA, many validated lncRNAs, such as HOTAIR, GAS5, and HIX003209, have been identified as promising novel biomarkers for both diagnosis and treatment. The shared lncRNAs, for example, GAS5, may participate in SLE pathogenesis through the mitogen-activated protein kinase pathway and trigger the AMP-activated protein kinase pathway in RA. Here, we summarize the data on key lncRNAs that may drive the pathogenesis of SLE and RA and could potentially serve as emerging novel biomarkers and therapeutic targets in the coming future.